Histological and Histomorphomitrical Evaluation of Rabbit Oral Cavity Wound Healing by Feeding Absorbable Amino Acid - Manar Abd Alrazaq Hassan (Diyala Journal of Medicine, 2024)
Background: Traumatic oral ulcer is well-circumscribed, depressed lesion with an epithelial defect that is covered by a fibrin clot, resulting in a yellow-white appearance, occurs due to chemical, mechanical or thermal injury to oral mucosal end with painful erosion. Amino acids are necessary for wound healing because they promote the growth of connective tissue as well as the activation and proliferation of fibroblasts. Objective: evaluation the effect of systemic application of amino acid collection (oral intake) in treatment of traumatic oral ulceration over selected time by histological and histomorophometric assessment of soft tissue healing. Patients and Methods: 20 adult male rabbits that weight about 700-900 Kg and age about (6-8) months where used in this experimental study. The traumatic ulcer created with (8mm) diameter, and (1mm) by surgical round diamond bur in the right cheek mucosa, then divided the groups in two groups,10 rabbits for control group that left healed normally , and 10 rabbits for experimental group that daily used mixture of amino acids systemically through mixing with water for one month. The animals were sacrificed along 3 and 7 days healing periods and the species examined histologically after histological preparation of the traumatic ulcer. Results: Histological and histomorphometeric findings showed decreased inflammation, accelerated reepithelization of ulcer surface, better angiogenesis, and promoted remodeling of the extracellular matrix resulting with enhanced tissue maturation and complete healing in all study groups than in the control group. Conclusion: the chemical medicament that represented by systemic application of amino acid effective in accelerating the healing of traumatized ulcers in experimental group than that in control group by accelerated cell proliferation and mucosa reepithelization. Keywords: Traumatic ulcers, amino acid, reepithelization.